2012
DOI: 10.1002/aenm.201200079
|View full text |Cite
|
Sign up to set email alerts
|

Round‐Robin Studies as a Method for Testing and Validating High‐Efficiency ITO‐Free Polymer Solar Cells Based on Roll‐to‐Roll‐Coated Highly Conductive and Transparent Flexible Substrates

Abstract: COMMUNICATION 1091 wileyonlinelibrary.com www.MaterialsViews.com www.advenergymat.dePhotovoltaic cells [ 1 ] based on organic and polymer materials (OPVs) are celebrated as being a possible solution to the energy needs of the future, [ 1b ] and, with record effi ciencies having breached the 10% milestone accompanied by emerging involvement from the materials industry, expectations are rapidly approaching reality. [ 1c ] However, in order to move OPVs beyond the individual laboratory and into a generally appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
0
38
1
Order By: Relevance
“…[12][13][14] Larsen- Olsen et al showed that the use of high-conductive PEDOT:PSS with or without a preprocessed silver collecting grid can be used as a substitute for ITO in inverted structure devices and modules with good results. 12,14 By appliance of a short pulse at high negative bias to the solar cell, it is possible to electrochemically ''switch'' (reduce) a thin layer of the top PEDOT causing a permanent conductivity change rendering it a rectifying junction.…”
Section: Krebs Et Al Introduced a New Fabrication Methods For All R2rmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Larsen- Olsen et al showed that the use of high-conductive PEDOT:PSS with or without a preprocessed silver collecting grid can be used as a substitute for ITO in inverted structure devices and modules with good results. 12,14 By appliance of a short pulse at high negative bias to the solar cell, it is possible to electrochemically ''switch'' (reduce) a thin layer of the top PEDOT causing a permanent conductivity change rendering it a rectifying junction.…”
Section: Krebs Et Al Introduced a New Fabrication Methods For All R2rmentioning
confidence: 99%
“…[12][13][14] Larsen- Olsen et al showed that the use of high-conductive PEDOT:PSS with or without a preprocessed silver collecting grid can be used as a substitute for ITO in inverted structure devices and modules with good results. 12,14 By appliance of a short pulse at high negative bias to the solar cell, it is possible to electrochemically ''switch'' (reduce) a thin layer of the top PEDOT causing a permanent conductivity change rendering it a rectifying junction. Further studies on the use of different types of front grids in the same process were carried out by Yu et al showing that thermally embedded silver grids and flexo printed silver grids result in solar cells with similar efficiencies (slightly better for the embedded grid), whereas solar modules with inkjet printed silver front grid performed poorer, which was ascribed to the lower conductivity of the grid.…”
Section: Krebs Et Al Introduced a New Fabrication Methods For All R2rmentioning
confidence: 99%
“…In particular, organic solar cells (OSCs) have been the focus of research in the past decade due to some advantages such as simple preparation with ambient temperature and pressure, low cost, light weight and fl exibility. [1][2][3][4][5][6] In recent years, numerous literatures focused on design and synthesis of donor materials, [7][8][9][10][11][12][13][14] fullerene derivative or non-fullerene acceptor materials, [15][16][17][18] optimization of device performance [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and roll-to-roll coating techniques; [36][37][38] these efforts have promoted power conversion effi ciency (PCE) of OSCs exceeding 9%. [39][40][41][42][43] Lateral and vertical phase separation is very important to OSCs, [44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…Organic electronics remains an active area of research and development, mainly due to the potential low-cost production [1], [2], [3], flexibility [4], [5] or semitransparency [6], [7]. Firstly, applications in modern science, e.g.…”
Section: Introductionmentioning
confidence: 99%